What's your digital business model? : - Weill, Peter (Harvard Business Review Press, 2018)
What is your digital business model? While many leaders of companies recognize the threat from digital--and the potential opportunity--they lack a common language or a compelling framework to help them assess it and, more importantly, to direct them. They don't know how to think about their digital business model. In this probing and practical book, Peter Weill and Stephanie Woerner provide much-needed tools, self-assessments, motivating examples, and key financial analyses of where the profits will likely be made. Based on five years of study at the MIT Center for Information Systems Research, the book provides a powerful yet simple framework that has been field-tested globally with more than a dozen senior management teams. The authors found that digitization is moving companies' business models on two dimensions: from value chains to digital ecosystems, and from a fuzzy understanding of the needs of end customers to a sharper one. Looking at these dimensions in combination results in four distinct business models, each with different capabilities: (1) Supplier, (2) Omni-channel, (3) Modular Producer, and (4) Ecosystem Driver. The framework helps companies clarify where they are currently in an increasingly digital business landscape and highlights what's needed to move toward another, higher-value digital business model. In meeting the growing challenge to "go digital," this smart book will help you grapple with the threats, respond to the opportunities, and create winning digital strategies.